2020
DOI: 10.1097/rlu.0000000000003060
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Imaging of Vasculitis Complicated With Relapsing Polychondritis

Abstract: We present a case of a 38-year-old woman who complained with cough, fever, and back pain with a weight loss. 18F-FDG PET/CT to search fever origin revealed uptake in the tracheobronchial and the left auricular cartilage and wall of the thoracic aorta. She underwent biopsy of the left auricle and was diagnosed with relapsing polychondritis (RP) complicating vasculitis. After steroid therapy, FDG PET/CT demonstrated regression of inflammation, showing decreases in the uptakes. Vasculitis should be considered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Prior studies have shown that 18 F-fluoro-2-deoxyglucose positron emission tomography (FDG-PET)/CT images exhibited the characteristic features of relapsing polychondritis. 19,20 Chen et al . conducted a review of 28 relapsing polychondritis patients with airway involvement, all of whom underwent PET/CT examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that 18 F-fluoro-2-deoxyglucose positron emission tomography (FDG-PET)/CT images exhibited the characteristic features of relapsing polychondritis. 19,20 Chen et al . conducted a review of 28 relapsing polychondritis patients with airway involvement, all of whom underwent PET/CT examination.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that 18 F-fluoro-2-deoxyglucose positron emission tomography (FDG-PET)/CT images exhibited the characteristic features of relapsing polychondritis. 19,20 Chen et al conducted a review of 28 relapsing polychondritis patients with airway involvement, all of whom underwent PET/CT examination. 21 Twenty-four PET/CT scans of the tracheal and bronchial trachea revealed augmented density, tube wall oedema, thickening and calcification, and limited stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no diagnostic standard sensitive enough to reach 100%[ 13 ]. Imaging examinations, such as CT, positron emission tomography–CT, tracheobronchoscopy, electronic fiber nasolaryngoscopy, and lung function and pathology could be included as auxiliary diagnostic criteria to improve early diagnostic sensitivity[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%